Enhancing Readiness and Mathematics Performance in Face-to-Face Learning Among Grade 7 Students: A Descriptive-Correlational Study - Conrado A Batiao; Alberto D Yazon; Karen A Manaig; Sherwin B Sapin; Victoria E Tamban (Research Synergy Foundation, 2023)
This study aimed to determine the relationship between the level of readiness and mathematics performance in face-to-face learning among Grade 7 learners at Balibago Integrated High School. This study employed a descriptive-correlational design to determine the correlation between the two variables under consideration. A stratified proportionate random sampling technique was used to determine the sample from the population of learners, and the number of samples was established using the Cochran formula. The study employed a researcher-designed questionnaire to assess learners' readiness levels and mathematics performance, which was verified by a panel of experts in the field. The questionnaire on readiness focused on measuring students' cognitive, social, physical, and emotional aspects. The gathered data were evaluated using frequency counts and percentages, mean, standard deviation, Pearson's r, and hierarchical multiple regression. Based on the findings, it showed that learners' levels of cognitive, social, and physical readiness were high but only moderate emotionally. Nonetheless, students' mathematics performance was poor because the computed mean fell within a low range. Thus, the findings revealed a strong and positive correlation between students' readiness and mathematics performance, with a p-value of 0.007, which rejected the null hypothesis. However, the findings revealed that there was no substantial moderating influence on the profile of learners' mathematics performance about their readiness, with a p-value greater than .01. In light of this, a learner's level of preparedness in terms of cognitive, social, emotional, and physical factors may have an impact on how well they perform mathematically.